Merger options and risk arbitrage - Peter Van Tassel (Federal Reserve Bank of New York, 2016)
Option prices embed predictive content for the outcomes of pending mergers and acquisitions. This is particularly important in merger arbitrage, where deal failure is a key risk. In this paper, I propose a dynamic asset pricing model that exploits the joint information in target stock and option prices to forecast deal outcomes. By analyzing how deal announcements affect the level and higher moments of target stock prices, the model yields better forecasts than existing methods. In addition, the model accurately predicts that merger arbitrage exhibits low volatility and a large Sharpe ratio when deals are likely to succeed.
Keywords: G00; G12; G34; 330; financial economics; option pricing; mergers and acquisitions